Comparative efficacy of electrokinetic and static leaching for selective metal recovery and nutrient release from porphyry Cu tailings - Yujie Yan; Gawen R.T. Jenkin; Andrew P. Abbott; Alexandria Tanciongco; Carlo A. Arcilla; Cris Reven L. Gibaga; Daniel J. Smith; Djoan Kate Tungpalan; Jonathan E. Chambers; John Henry C. Gervasio; James Symons; Justine Perry T. Domingo; et al. (Chemical Engineering Journal, 2026)

National-scale river water quality in the Philippines: establishing baselines in a mineralised megadiverse nation - Emma Biles; Richard David Williams; Decibel Faustino-Eslava; Loucel Cui; Francis Ian Gonzalvo; Kim Bryan Cabrera; Manilyn Casa; Craig MacDonell; Maria Regina V. Regalado; Laura Quick; Justine Perry Domingo; Trevor Hoey; et al. (Science of The Total Environment, 2026)

Genome-resolved metagenomics uncovers antimicrobial resistance gene carriers in hospital and municipal wastewater environments - Reshma Silvester; Gordon Webster; William B. Perry; Kata Farkas; Laura Rushton; Noel Craine; Gareth Cross; Peter Kille; Andrew J. Weightman; Davey L. Jones (Science of The Total Environment, 2025)

Metagenomics unveils the role of hospitals and wastewater treatment plants on the environmental burden of antibiotic resistance genes and opportunistic pathogens - Reshma Silvester; William B. Perry; Gordon Webster; Laura Rushton; Amy Baldwin; Daniel A. Pass; Nathaniel Healey; Kata Farkas; Noel Craine; Gareth Cross; Peter Kille; Andrew J. Weightman; et al. (Science of The Total Environment, 2025)

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

National-scale antimicrobial resistance surveillance in wastewater: A comparative analysis of HT qPCR and metagenomic approaches - Margaret E. Knight; Gordon Webster; William B. Perry; Amy Baldwin; Laura Rushton; Daniel A. Pass; Gareth Cross; Isabelle Durance; Windi Muziasari; Peter Kille; Kata Farkas; Andrew J. Weightman; et al. (Water Research, 2024)

Sustainable mining in tropical, biodiverse landscapes: Environmental challenges and opportunities in the archipelagic Philippines - Justine Perry T. Domingo; Gawen R.T. Jenkin; Laura Quick; Richard D. Williams; Karen A. Hudson-Edwards; Cecilia Tortajada; Patrick Byrne; Tom J. Coulthard; Jenielyn T. Padrones; Rich Crane; Cris Reven L. Gibaga; Grigorios Vasilopoulos; et al. (Journal of Cleaner Production, 2024)

Is our understanding of aquatic ecosystems sufficient to quantify ecologically driven climate feedbacks? - Corday R. Selden; Richard LaBrie; Laura C. Ganley; Daniel R. Crocker; Ohad Peleg; Danielle C. Perry; Hannah G. Reich; Matthew Sasaki; Patricia S. Thibodeau; Jana Isanta‐Navarro (Global Change Biology, 2024)
The Earth functions as an integrated system—its current habitability to complex life is an emergent property dependent on interactions among biological, chemical, and physical components. As global warming affects ecosystem structure and function, so too will the biosphere affect climate by altering atmospheric gas composition and planetary albedo. Constraining these ecosystem‐climate feedbacks is essential to accurately predict future change and develop mitigation strategies; however, the interplay among ecosystem processes complicates the assessment of their impact. Here, we explore the state‐of‐knowledge on how ecological and biological processes (e.g., competition, trophic interactions, metabolism, and adaptation) affect the directionality and magnitude of feedbacks between ecosystems and climate, using illustrative examples from the aquatic sphere. We argue that, despite ample evidence for the likely significance of many, our present understanding of the combinatorial effects of ecosystem dynamics precludes the robust quantification of most ecologically driven climate feedbacks. Constraining these effects must be prioritized within the ecological sciences for only by studying the biosphere as both subject and arbiter of global climate can we develop a sufficiently holistic view of the Earth system to accurately predict Earth's future and unravel its past.

Correlating the role of nanofillers with active layer properties and performance of thin-film nanocomposite membranes - Lamar A. Perry; Nick Guan Pin Chew; Kasia Grzebyk; Pinar Cay-Durgun; Mary Laura Lind; Paban Sitaula; Mustapha Soukri; Orlando Coronell (Desalination, 2023)

Lymphomatosis as a Cause of Abdominal Pain and Distension in Two Adult Horses - Laura R. Perry; Amanda J. Butler; Emily John; Shannon Martinson; Melanie Buote; Kimberley Foote; Shelley Burton; William B. Stoughton (Journal of Equine Veterinary Science, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Invasion of Siberian Elm (Ulmus pumila) Along the South Platte River: the Roles of Seed Source, Human Influence, and River Geomorphology - Lindsay V. Reynolds; Laura G. Perry; Patrick B. Shafroth; Gabrielle Katz; Andrew Norton (Wetlands, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Escaping the fate of Sisyphus: assessing resistome hybridization baits for antimicrobial resistance gene capture - Megan S. Beaudry; Jesse C. Thomas; Rodrigo P. Baptista; Amanda H. Sullivan; William Norfolk; Alison Devault; Jacob Enk; Troy J. Kieran; Olin E. Rhodes; K. Allison Perry‐Dow; Laura J. Rose; Natalia J. Bayona‐Vásquez; et al. (Environmental Microbiology, 2021)
Summary Finding, characterizing and monitoring reservoirs for antimicrobial resistance (AMR) is vital to protecting public health. Hybridization capture baits are an accurate, sensitive and cost‐effective technique used to enrich and characterize DNA sequences of interest, including antimicrobial resistance genes (ARGs), in complex environmental samples. We demonstrate the continued utility of a set of 19 933 hybridization capture baits designed from the Comprehensive Antibiotic Resistance Database (CARD)v1.1.2 and Pathogenicity Island Database (PAIDB)v2.0, targeting 3565 unique nucleotide sequences that confer resistance. We demonstrate the efficiency of our bait set on a custom‐made resistance mock community and complex environmental samples to increase the proportion of on‐target reads as much as >200‐fold. However, keeping pace with newly discovered ARGs poses a challenge when studying AMR, because novel ARGs are continually being identified and would not be included in bait sets designed prior to discovery. We provide imperative information on how our bait set performs against CARDv3.3.1, as well as a generalizable approach for deciding when and how to update hybridization capture bait sets. This research encapsulates the full life cycle of baits for hybridization capture of the resistome from design and validation (both in silico and in vitro ) to utilization and forecasting updates and retirement.

Spatiotemporal patterns of ENSO‐precipitation relationships in the tropical Andes of southern Peru and Bolivia - Joseph A. Jonaitis; L. Baker Perry; Peter T. Soulé; Christopher Thaxton; Marcos F. Andrade‐Flores; Tania Ita Vargas; Laura Ticona (International Journal of Climatology, 2021)
Precipitation in the outer tropical Andes is highly seasonal, exhibits considerable interannual variability, and is vital for regulating freshwater availability, flooding, glacier mass balance, and droughts. The primary driver of interannual variability is El Niño Southern Oscillation (ENSO), with most investigations reporting that the El Niño (La Niña) results in negative (positive) precipitation anomalies across the region. Recent investigations, however, have identified substantial spatiotemporal differences in ENSO‐precipitation relationships. Motivated by the dissimilarity of these findings, this study examines a carefully selected data set (≥ 90% completeness) of ground‐based precipitation observations from 75 high‐elevation (≥ 2,500 m above sea level) meteorological stations in the tropical Andes of southern Peru and Bolivia for the period 1972–2016. Distinct groups of stations and associated variability in precipitation characteristics (e.g., total seasonal precipitation, wet season onset, and wet season length) are identified. Using no spatial constraints, the K‐Means algorithm optimally grouped stations into five easily identifiable groups. The groups farthest from the Amazon basin had significant negative (positive) precipitation anomalies ( p

Larval cross‐shore transport estimated from internal waves with a background flow: The effects of larval vertical position and depth regulation - Jessica C. Garwood; Andrew J. Lucas; Perry Naughton; Paul L. D. Roberts; Jules S. Jaffe; Laura deGelleke; Peter J. S. Franks (Limnology and Oceanography, 2021)
Cross‐shore velocities in the coastal ocean typically vary with depth. The direction and magnitude of transport experienced by meroplanktonic larvae will therefore be influenced by their vertical position. To quantify how swimming behavior and vertical position in internal waves influence larval cross‐shore transport in the shallow (~ 20 m), stratified coastal waters off Southern California, we deployed swarms of novel, subsurface larval mimics, the Mini‐Autonomous Underwater Explorers (M‐AUEs). The M‐AUEs were programmed to maintain a specified depth, and were deployed near a mooring. Transport of the M‐AUEs was predominantly onshore, with average velocities up to 14 cm s −1 . To put the M‐AUE deployments into a broader context, we simulated > 500 individual high‐frequency internal waves observed at the mooring over a 14‐d deployment; in each internal wave, we released both depth‐keeping and passive virtual larvae every meter in the vertical. After the waves' passage, depth‐keeping virtual larvae were usually found closer to shore than passive larvae released at the same depth. Near the top of the water column (3–5‐m depth), ~ 20% of internal waves enhanced onshore transport of depth‐keeping virtual larvae by ≥ 50 m, whereas only 1% of waves gave similar enhancements to passive larvae. Our observations and simulations showed that depth‐keeping behavior in high‐frequency internal waves resulted in enhanced onshore transport at the top of the water column, and reduced offshore dispersal at the bottom, compared to being passive. Thus, even weak depth‐keeping may allow larvae to reach nearshore adult habitats more reliably than drifting passively.

Cytokinin activity during early kernel development corresponds positively with yield potential and later stage ABA accumulation in field-grown wheat (Triticum aestivum L.) - Hai Ngoc Nguyen; Laura Perry; Anna Kisiala; Henry Olechowski; R. J. Neil Emery (Planta, 2020)

The role of psychology in determining human–predator conflict across southern Kenya - Laura R. Perry; Tom P. Moorhouse; Andrew J. Loveridge; David W. Macdonald (Conservation Biology, 2020)
Conflict between people and carnivores can lead to the widespread killing of predators in retaliation for livestock loss and is a major threat to predator populations. In Kenya, a large, rural, pastoralist population comes into regular conflict with predators, which persist across southern Kenya. We explored the social and psychological backdrop to livestock management practices in this area in a process designed to be easy to use and suitable for use across large areas for the study of conflict and transboundary implementation of wildlife conflict reduction measures, focusing on community involvement and needs. We carried out fully structured interviews of livestock managers with a survey tool that examined how social and psychological factors may influence livestock management behavior. We compared survey responses on 3 sites across the study area, resulting in 723 usable responses. Efficacy of individuals’ livestock management varied between and within communities. This variation was partially explained by normative and control beliefs regarding livestock management. Individual livestock managers’ self‐reported management issues were often an accurate reflection of their practical management difficulties. Psychological norms, control beliefs, and attitudes differed among sites, and these differences partially explained patterns associated with conflict (i.e., variation in livestock management behavior). Thus, we conclude that a one‐size‐fits‐all approach to improving livestock management and reducing human–predator conflict is not suitable.

A novel cross‐shore transport mechanism revealed by subsurface, robotic larval mimics: Internal wave deformation of the background velocity field - Jessica C. Garwood; Andrew J. Lucas; Perry Naughton; Matthew H. Alford; Paul L. D. Roberts; Jules S. Jaffe; Laura deGelleke; Peter J. S. Franks (Limnology and Oceanography, 2020)
Coastal physical processes are essential for the cross‐shore transport of meroplanktonic larvae to their benthic adult habitats. To investigate these processes, we released a swarm of novel, trackable, subsurface vehicles, the Mini‐Autonomous Underwater Explorers (M‐AUEs), which we programmed to mimic larval depth‐keeping behavior. The M‐AUE swarm measured a sudden net onshore transport of 30–70 m over 15–20 min, which we investigated in detail. Here, we describe a novel transport mechanism of depth‐keeping plankton revealed by these observations. In situ measurements and models showed that, as a weakly nonlinear internal wave propagated through the swarm, it deformed surface‐intensified, along‐isopycnal background velocities downward, accelerating depth‐keeping organisms onshore. These higher velocities increased both the depth‐keepers' residence time in the wave and total cross‐shore displacement, leading to wave‐induced transports twice those of fully Lagrangian organisms and four times those associated with the unperturbed background currents. Our analyses also show that integrating velocity time series from virtual larvae or mimics moving with the flow yields both larger and more accurate transport estimates than integrating velocity time series obtained at a point (Eulerian). The increased cross‐shore transport of organisms capable of vertical swimming in this wave/background‐current system is mathematically analogous to the increase in onshore transport associated with horizontal swimming in highly nonlinear internal waves. However, the mechanism described here requires much weaker swimming speeds (mm s −1 vs. cm s −1 ) to achieve significant onshore transports, and meroplanktonic larvae only need to orient themselves vertically, not horizontally.

Temporal relationship between the Lassen volcanic center and mafic regional volcanism - Aurelie Germa; Chris Perry; Xavier Quidelleur; Andrew Calvert; Michael Clynne; Charles B. Connor; Laura J. Connor; Rocco Malservisi; Sylvain Charbonnier (Bulletin of Volcanology, 2019)

Divergent effects of land-use, propagule pressure, and climate on woody riparian invasion - Laura G. Perry; Lindsay V. Reynolds; Patrick B. Shafroth (Biological Invasions, 2018)

Riparian Soil Development Linked to Forest Succession Above and Below Dams Along the Elwha River, Washington, USA - Laura G. Perry; Patrick B. Shafroth; Steven S. Perakis (Ecosystems, 2017)

Vulnerability of riparian ecosystems to elevated CO 2 and climate change in arid and semiarid western N orth A merica - Laura G. Perry; Douglas C. Andersen; Lindsay V. Reynolds; S. Mark Nelson; Patrick B. Shafroth (Global Change Biology, 2012)
Riparian ecosystems, already greatly altered by water management, land development, and biological invasion, are being further altered by increasing atmospheric CO 2 concentrations ([ CO 2 ]) and climate change, particularly in arid and semiarid (dryland) regions. In this literature review, we (1) summarize expected changes in [ CO 2 ], climate, hydrology, and water management in dryland western N orth A merica, (2) consider likely effects of those changes on riparian ecosystems, and (3) identify critical knowledge gaps. Temperatures in the region are rising and droughts are becoming more frequent and intense. Warmer temperatures in turn are altering river hydrology: advancing the timing of spring snow melt floods, altering flood magnitudes, and reducing summer and base flows. Direct effects of increased [ CO 2 ] and climate change on riparian ecosystems may be similar to effects in uplands, including increased heat and water stress, altered phenology and species geographic distributions, and disrupted trophic and symbiotic interactions. Indirect effects due to climate‐driven changes in streamflow, however, may exacerbate the direct effects of warming and increase the relative importance of moisture and fluvial disturbance as drivers of riparian ecosystem response to global change. Together, climate change and climate‐driven changes in streamflow are likely to reduce abundance of dominant, native, early‐successional tree species, favor herbaceous species and both drought‐tolerant and late‐successional woody species (including many introduced species), reduce habitat quality for many riparian animals, and slow litter decomposition and nutrient cycling. Climate‐driven changes in human water demand and associated water management may intensify these effects. On some regulated rivers, however, reservoir releases could be managed to protect riparian ecosystem. Immediate research priorities include determining riparian species' environmental requirements and monitoring riparian ecosystems to allow rapid detection and response to undesirable ecological change.

Immobilizing nitrogen to control plant invasion - Laura G. Perry; Dana M. Blumenthal; Thomas A. Monaco; Mark W. Paschke; Edward F. Redente (Oecologia, 2010)

Native cover crops suppress exotic annuals and favor native perennials in a greenhouse competition experiment - Laura G. Perry; Spencer A. Cronin; Mark W. Paschke (Plant Ecology, 2009)

Concentrations of the Allelochemical (±)-Catechin IN Centaurea maculosa Soils - Laura G. Perry; Giles C. Thelen; Wendy M. Ridenour; Ragan M. Callaway; Mark W. Paschke; Jorge M. Vivanco (Journal of Chemical Ecology, 2007)

No evidence for root-mediated allelopathy in Centaurea solstitialis, a species in a commonly allelopathic genus - Bo Qin; Jennifer A. Lau; Joseph Kopshever; Ragan M. Callaway; Heather McGray; Laura G. Perry; Tiffany L. Weir; Mark W. Paschke; Jose L. Hierro; John Yoder; Jorge M. Vivanco; Sharon Strauss (Biological Invasions, 2007)

Light competition for invasive species control: A model of cover crop–weed competition and implications for Phalaris arundinacea control in sedge meadow wetlands - Laura G. Perry; Susan M. Galatowitsch (Euphytica, 2006)

Zinc Toxicity Thresholds for Reclamation Forb Species - Mark W. Paschke; Laura G. Perry; Edward F. Redente (Water, Air, & Soil Pollution, 2006)

The influence of light availability on competition between Phalaris arundinacea and a native wetland sedge - Laura G. Perry; Susan M. Galatowitsch (Plant Ecology, 2004)

The major brain isoform of Kif1b lacks the putative mitochondria-binding domain - Laura Conforti; E. Anne Buckmaster; Andrea Tarlton; Michael C. Brown; Mary F. Lyon; V. Hugh Perry; Michael P. Coleman (Mammalian Genome, 1999)

Biopharmaceutical Approaches for Developing and Assessing Oral Peptide Delivery Strategies and Systems: In Vitro Permeability and In Vivo Oral Absorption of Salmon Calcitonin - Patrick J. Sinko; Yong-Hee Lee; Vijaya Makhey; Glen D. Leesman; John P. Sutyak; Hongshi Yu; Barbara Perry; Curtis L. Smith; Peidi Hu; Erik J. Wagner; Lisa M. Falzone; Laura T. McWhorter; et al. (Pharmaceutical Research, 1999)